GAMBARAN KELELAHAN KERJA KARYAWAN KONSTRUKSI PT SCU DESA SILAM TAHUN 2021 - Lira Mufti Azzahri Isnaeni; Etri Gustriana (KOLONI, 2022)
International Indonesia several environmental factors that affect the occurrence of work stress, such as the environment, vibration, lighting and dust. One of the causes that affect the occurrence of work stress in workers is fatigue. This type of research is an interview method using a descriptive approach with the aim of obtaining information about the description of fatigue experienced by workers at the factory of PT. SCU Desa Silam in 2021 by conducting interviews through the Swedish Occupational Fatigue Inventory (SOFI) questionnaire, namely the Swedish work fatigue inventory. This research was conducted in Silam Village. This research was conducted on 10 - 17 December 2021. The population of this study were all workers at the factory of PT. Silam Village SCU in 2021 based on observations, namely as many as 422 people divided into each factory, namely Factory 0 (33 people), Factory 1 (54 people), Factory 2 (75 people), Factory 3 (117 people), Factory 4 (64 people), Factory 5 (49 people), Factory 6 (30 people). The object studied in this study were workers at PT. SCU Desa Silam Factory section. The sample in this study was 205 respondents. From the results of the study, it was found that based on the energy level of the factory workers at PT. SCU, for the category that lacks energy, out of 205 respondents, 111 respondents (54.1%) experienced work fatigue. Based on the physical ability of factory workers at PT. SCU, for the category of workers who have small physical abilities, out of 205 respondents, 71 respondents (34.6%) experienced work fatigue. Based on the physical comfort of factory workers at PT. SCU, for the category of workers who are not comfortable working, out of 205 respondents, 106 respondents (51.7%) experienced work fatigue. Based on the motivation of factory workers at PT. SCU, for the category of workers who are less motivated than 205 respondents, 64 respondents (31.2%) experienced work fatigue. Based on the drowsiness of factory workers at PT. Maruki Internasional Indonesia, for the category of workers who experience fatigue, out of 205 respondents, 108 respondents (52.6%) experienced fatigue. Keywords: work fatigue, construction